2023
DOI: 10.1002/cb.2144
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable mobility choices: Exploring the impact of consumers' values, attitudes, perceived behavioural control and subjective norms on the likelihood to choose sustainable mobility options

Abstract: This study explores consumers' behaviour regarding sustainable mobility options. A mixed‐methods approach was adopted to examine the impact of bio‐altruistic values, egoistic values, environmental attitudes, attitudes regarding sustainable mobility, perceived behavioural control and subjective norms on the likelihood of choosing sustainable mobility options. To collect the data, an online survey was applied to a sample of 645 Portuguese consumers, which included one single non‐mandatory open‐ended question to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…In COVID-19 pandemic, many scholars demonstrated that subjective norms can significantly promote the formation of willingness to purchase organic food. Consumers may also be influenced by the government or social groups [ 41 ]. However, there have been limited discussions on moral norms in existing studies.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…In COVID-19 pandemic, many scholars demonstrated that subjective norms can significantly promote the formation of willingness to purchase organic food. Consumers may also be influenced by the government or social groups [ 41 ]. However, there have been limited discussions on moral norms in existing studies.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…The construct of perceived behavioural control (PBC) has provided a solid theoretical underpinning when studying consumers' willingness to undertake new behaviours such as sustainable mobility. This is the focus of the paper 'Sustainable Mobility Choices: Exploring the Impact of Consumers' values, Attitudes, Perceived Behavioural Control and Subjective Norms on the Likelihood to Choose Sustainable Mobility Options' by Nogueira et al (2023), but they compare and control for the role of other attitudinal and affective variables vis a vis PBC when it comes to consumers' decision to consider more environmentally friendly mobility options. A particular feature of their paper is that, in addition to applying regression modelling, they also complement their insights with a content and thematic analysis using open ended responses from their survey.…”
Section: Dear Editormentioning
confidence: 99%
“…Similarly, in the case of sustainable consumption, it refers to the individual perception of his own ability to follow sustainable consumption behaviour (Ricci et al, 2018). This perception may be dependent upon the factors that are internal (such as confidence, skills, the capability to pursue behaviour) or external (such as available resources, efforts, time or cost involved) to the individual, but are found to directly or indirectly influence his/her consumption intentions (Armitage & Conner, 1999;Nogueira et al, 2023). Also, individuals with resources required to display a particular behaviour, have stronger behavioural intentions to perform that behaviour (Carri on B osquez et al, 2023;White Baker et al, 2007).…”
Section: Perceived Behavioural Control and Sustainable Consumption In...mentioning
confidence: 99%
“…Subjective norms are also found to play a significant role in guiding the customer's purchase intention and direct them to differentiate between what is acceptable and not acceptable (Joshi et al, 2019; Venciute et al, 2023; Xie & Madni, 2023). It is considered as a powerful predictor of environmental behaviour and exerts a strong impact on consumer's behavioural intention (Ali et al, 2023; Ayar & Gürbüz, 2021; Ceglia et al, 2015; Ishaq et al, 2021; Nogueira et al, 2023). Also, subjective norms substantially contribute to an individual's lifestyle choices such as being ecologically responsible, purchasing wisely, think sustainably and so forth.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%